John Fitch papers - Fitch, John, 1743-1798.; Thornton, William, 1759-1828.
Correspondence, diaries, financial papers, surveyor's notes, steamboat sketches, drafts of writings, printed matter, and miscellany. The papers relate chiefly to Fitch's development and promotion of the steamboat, though there is also material relating to his earlier surveying work in Ohio. Also includes some papers of architect William Thornton (1759-1828). Correspondents include Joshua Anderson, John James Beckley, Robert Fulton, Josiah Hornblower, Thomas Hutchins, Thomas Johnson, William Samuel Johnson, Jonathan Longstreth, Thomas Mifflin, Robert Morris, Charles Pettit, Edmund Randolph, Caleb S. Riggs, David Rittenhouse, Benjamin Say, and William Thornton.
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
Inventor.
Finding aid available in the Library of Congress Manuscript Reading Room.
Forms part of: Peter Force papers and collection (Series 8D : entry 47).
Keywords: Anderson, Joshua -- Correspondence; Beckley, John James, -- 1757-1807 -- Correspondence; Fulton, Robert, -- 1765-1815 -- Correspondence; Hornblower, Josiah, -- 1729-1809 -- Correspondence; Hutchins, Thomas, -- 1730-1789 -- Correspondence; Johnson, Thomas, -- 1732-1819 -- Correspondence; Johnson, William Samuel, -- 1727-1819 -- Correspondence; Longstreth, Jonathan -- Correspondence; Mifflin, Thomas, -- 1744-1800 -- Correspondence; Morris, Robert, -- 1734-1806 -- Correspondence; Pettit, Charles, -- 1736-1806 -- Correspondence; Randolph, Edmund, -- 1753-1813 -- Correspondence; Riggs, Caleb S. -- 1756-1825 -- Correspondence; Rittenhouse, David, -- 1732-1796 -- Correspondence; Say, Benjamin, -- 1755-1813 -- Correspondence; Steamboats; Surveying -- Ohio; Inventors